SCALE DEVELOPMENT STAGES SPECIFIC TO HEALTH LITERACY - Nayir, Tufan (Turkey Health Literacy Journal, 2023)
This review was written by following the scale development stages specific to health literacy, in order to help academicians who will develop a scale approach systematically, and also to facilitate their studies by providing easier access to information on the subject.
Keywords: Health literacy, scale development